THE EFFECT OF MOUTHWASH COMBINATION OF IMMUNOGLOBULIN-Y ANTI-COMD STREPTOCOCCUS MUTANS AND CHITOSAN ON THE FORMATION OF STREPTOCOCCUS MUTANS BIOFILM - BACHTIAR, ENDANG WINIATI; APRITANTIA, DETA; SARWONO, AGOENG TJAHAJANI; BACHTIAR, BOY M.; SOEJOEDONO, RETNO D.; WIBAWAN, I. WAYAN TEGUH (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to investigate the effectiveness of immunoglobulin Y (IgY) antibodies as a dental caries vaccine by utilizing IgY specific to the quorum-sensing signaling receptor ComD of Streptococcus mutans combined with chitosan in the form of mouthwash. Methods: The effects of a mouthwash containing IgY anti-ComD S. mutans with and without chitosan on biofilm-forming isolates of S. mutans were investigated. Subjects were assigned to rinsing twice daily for 6 days with 15–20 ml mouthwash solution for 30 s. Biofilm formation of S mutans isolated from the patiens was measured using a crystal violet method to determine the optical density at 490 nm. Results: The results indicated that mouthwash containing IgY anti-ComD S. mutans and chitosan significantly enhanced the biofilm formation of S. mutans. In mouthwash containing IgY anti-ComD S. mutans without chitosan, a reduction in biofilm formation was observed; however, this was not statistically significant. Conclusions: The mouthwash combination of IgY anti-ComD S. mutans and chitosan enhanced the biofilm formation ability of S. mutans isolated from caries and caries-free subjects. Further, research is needed to determine the appropriate concentrations of IgY anti-ComD S. mutans and chitosan required to effectively inhibit dental caries.